1,25-Dihydroxyvitamin D Inhibits LPS-Induced High-Mobility Group Box 1 (HMGB1) Secretion via Targeting the NF-E2-Related Factor 2–Hemeoxygenase-1–HMGB1 Pathway in Macrophages - Rao, Zebing; Zhang, Na; Xu, Ning; Pan, Ying; Xiao, Mengjun; Wu, Junxian; Zhou, Hong; Yang, Shuo; Chen, Yunzi (Frontiers in Immunology, 2017)
1,25-Dihydroxyvitamin D (1,25(OH)2D3) is recognized as a key mediator of inflammatory diseases, including sepsis. Clinical studies demonstrate that 1,25 (OH)2D3 protects patients from sepsis, but clinical treatment with 1,25(OH)2D3 is rare. In this study, we report that 1,25(OH)2D3 treatment has beneficial effects and improves the survival rate in an LPS-induced mouse sepsis model by blocking the secretion of high mobility group box 1 (HMGB1), a key late regulator of sepsis. LPS-induced HMGB1 secretion is attenuated by 1,25(OH)2D3 via blocking HMGB1 translocation from the nucleus to the cytoplasm in macrophages. 1,25(OH)2D3 can induce the expression of Haeme oxygenase-1 (HO-1), which is essential for blocking HMBG1 nuclear translocation and its secretion. When siHO-1 or an HO-1 inhibitor used, the effect of 1,25(OH)2D3 on inhibition of HMGB1 secretion is suppressed. Considering that HO-1 is a downstream gene of Nrf2, we further confirm that Nrf2 activation can be activated by 1,25(OH)2D3 upon LPS exposure. Together, we provide evidence that 1,25(OH)2D3 attenuates LPS-induced HMGB1 secretion via the Nrf2/HO-1 pathway in macrophages.